Existence Results of Fractional Neutral Integrodifferential Equations with Deviating Arguments - Kamalapriya, B.; Balachandran, K.; Annapoorani, N. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper we prove the existence of solutions of fractional neutral integrodifferential equations with deviating arguments by using the resolvent operators and fixed point theorem. Examples are discussed to illustrate the theory.